2020
DOI: 10.3390/coatings10101003
|View full text |Cite
|
Sign up to set email alerts
|

The Law of Parsimony and the Negative Charge of the Bubbles

Abstract: Why the bubbles are negatively charged? This is almost 100 years old question, which many scientists have striven and still are striving to answer using the latest developments of the MD simulations and various physical analytical methods. We scrutinize with this paper the basic literature on this topic and conduct our own analysis. Following the philosophical law of parsimony: “Entities should not be multiplied without necessity”, we assume that the simplest explanation is the right one. It is well known that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Several simulation studies alone or combined with experimental studies showed that hydroxide ions are adsorbed at the hydrophobic medium/water interface [ 101 , 107 , 111 , 112 , 121 ]. According to quantum mechanical calculations, gaseous carboxylic acids deprotonation at the interface would be inhibited by a kinetic barrier, unless OH − would be present.…”
Section: Emulsifier-free Oil/water Interface Organizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several simulation studies alone or combined with experimental studies showed that hydroxide ions are adsorbed at the hydrophobic medium/water interface [ 101 , 107 , 111 , 112 , 121 ]. According to quantum mechanical calculations, gaseous carboxylic acids deprotonation at the interface would be inhibited by a kinetic barrier, unless OH − would be present.…”
Section: Emulsifier-free Oil/water Interface Organizationmentioning
confidence: 99%
“…Recent calculation studies of adsorption energies of OH − and H 3 O + at the air/water interface showed that OH − adsorption is energetically favorable, whereas H 3 O + adsorption is unfavorable. HCO 3 − adsorption would be also favorable, but to a lesser extent than OH − [ 112 ].…”
Section: Emulsifier-free Oil/water Interface Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…These hypotheses of Buckley et al (2023) are not supported by experimental evidence, which is particularly important for the second mechanism because the hypothesis is novel. It is noted that air bubbles exhibit a slight negative charge (Karakashev & Grozev, 2020) which would favor the second mechanism over the first. However, the question of which mechanism is dominant for the various PFAS species is largely immaterial in the context of practical interventions to enhance the removal of short‐chain PFAS using adsorptive bubble separation processes.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we prefer to study a simpler system, i.e., the effect of the electrostatic repulsion between the bubbles on the foamability of an aqueous solution of nonionic frother (e.g., MIBC). The intrinsic negative surface potential of the bubbles in water at normal pH value is still not well understood, but it is proved that it depends on the pH value [53]. Their isoelectric point is at pH ≈ 4 [1,54].…”
Section: Introductionmentioning
confidence: 99%